PENGEMBANGAN MODUL E-LEARNING BERBASIS WEB DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN PADA MAHASISWA IKIP BUDI UTOMO MALANG - Abadi Abadi (LPPM STKIP PGRI Sidoarjo, 2018)
Research on the development of e-learning module in learning Pendidikan Pancasila dan Kewarganegaraan has a goal where the e-learning module into an alternative web-based teaching materials that are easily accessible and used IKIP Budi Utomo Malang students. The e-learning module is web-based learning Pendidikan Pancasila dan Kewarganegaraan intended for students IKIP Budi Utomo Malang where subjects Pendidikan Pancasila dan Kewarganegaraan be compulsory subject as the formation of characters berbudiutama college students who are in harmony with the vision of campus IKIP Budi Utomo Malang that is